Tumor budding as a standardized parameter in gastrointestinal carcinomas: more than just the colon. (June 2018) - Berg, Kyra; Schaeffer, David
Abstract Tumor budding, defined as single cells or clusters of less than five cells, is thought to be a histomorphologic marker of an aggressive tumor behavior mimicking the embryologic epithelial–mesenchymal transition, and has been well established in the past two decades as a poor prognostic factor in colorectal carcinoma. Slow uptake in routine reporting of this important pathologic prognostic feature was in part due to differing methods of assessment of budding reported in the literature, but has recently been clarified at a consensus conference on tumor budding in colorectal carcinoma. Tumor budding is also increasingly being reported as a useful pathologic prognostic feature in other gastrointestinal carcinomas, including esophageal squamous cell carcinoma and adenocarcinoma, gastric intestinal-type adenocarcinoma, pancreatic ductal adenocarcinoma, and ampullary adenocarcinoma. In this review, we will summarize the studies on tumor budding in gastrointestinal carcinomas, with a focus on the methods of assessment used and the potential clinical applications of the findings.